2018
DOI: 10.2147/cmar.s183488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed miRNAs in early-stage cervical cancer with lymph node metastasis across The Cancer Genome Atlas datasets

Abstract: Background and aimPrevious studies have suggested that lymph node metastasis (LNM) in early-stage cervical cancer (CESC) may affect the prognosis of patients and the outcomes of subsequent adjuvant therapy. However, research focused on miRNA expression in early-stage CESC patients with LNM remains limited. Therefore, it is necessary to identify prognostic miRNAs and determine their molecular mechanisms.MethodsWe evaluated the differentially expressed genes in early-stage CESC patients with LNM compared to pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Previous studies also reported that miR-200a is associated with the development of cancer (i.e., esophageal, breast, and endometrial), by targeting specific genes such as CRMP1, EPHA2, and PTEN [1719]. Notably, miR-509-2 was differentially expressed in early-stage cervical cancer and might serve as a diagnostic biomarker in these patients [20]. Also, miR-636 acted as a tumor suppressor miRNA, which might affect the tumorigenesis of hepatocellular carcinoma through the downregulation of Ras [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that miR-200a is associated with the development of cancer (i.e., esophageal, breast, and endometrial), by targeting specific genes such as CRMP1, EPHA2, and PTEN [1719]. Notably, miR-509-2 was differentially expressed in early-stage cervical cancer and might serve as a diagnostic biomarker in these patients [20]. Also, miR-636 acted as a tumor suppressor miRNA, which might affect the tumorigenesis of hepatocellular carcinoma through the downregulation of Ras [21].…”
Section: Discussionmentioning
confidence: 99%
“…Uterine cervical cancer (UCC) is among the most common malignancies diagnosed and is a leading etiology of malignant tumor deaths in young women worldwide [1]. In many developing countries, it causes more than a quarter of a million deaths annually because of grossly deficient treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Chen Q et al analyzed the differential expression of 422 miRNAs in 145 patients diagnosed with early-stage CC (including 32 LNM+ patients and 113 LNM− patients) in The Cancer Genome Atlas (TCGA) database. They found that 75 miRNAs were differentially expressed between the 2 sample groups [ 36 ]. Interestingly, our results are consistent for five miRNAs (miR-548, miR-379, miR-337, miR-487b, and miR-376c) and several gene targets associated with lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%